All about process : the theory and discourse of modern artistic labor - Grant, Kim, 1962- (The Pennsylvania State University Press, 2017)
"A study of the concept of artistic process in the Western tradition of the visual arts. Focuses on modern and contemporary art and analyzes the development of process as a discourse that increasingly locates the primary value of art in the artist's creative labor"--Provided by publisher